Joint admission control algorithm based on load transfer in heterogeneous networks - Weiwei XIA; Zhaoming DING; Lianfeng SHEN (Tongxin xuebao)
A load-transfer-based joint admission control (LJAC) algorithm in heterogeneous networks was proposed.The access requirements of users were admitted based on load balancing,the dynamic load transfer of traffics in the overlapping coverage areas of heterogeneous networks were introduced,and the influence of such factors as the layout of heterogeneous networks and the vertical handoff was considered in the algorithm.The integrated system of heterogeneous networks was modeled as a multidimensional Markov chain,the steady-state probabilities were obtained and the quality of service (QoS) performance metrics were derived.Based on the Poisson point process theory,the upper bound of capacity of the heterogeneous networks satisfying QoS limitations was obtained.The admission control parameters of the integrated system of heterogeneous networks were optimized in order to maximize the resource utilization rate as well as guaranteeing the QoS of users.The simulation results demonstrate lower traffic blocking probability,lower failure probability of vertical handoff requirements,and larger system capacity gain can be achieved by using the proposed LJAC algorithm.